2003
DOI: 10.1375/twin.6.1.7
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Cohort Comparison of the Outcome of Twin Versus Singleton Pregnancies in Flanders, Belgium

Abstract: To compare perinatal outcome of singleton versus twin pregnancies a matched cohort study was performed in Flanders, Belgium. All twins delivered in the region of Flanders during 1998–1999 were compared to singletons, matched for gestational age, fetal sex and maternal parity, resulting in 4384 infants in each group. Above 32 weeks of gestation, birthweight was significantly lower in twins (2095 ± 364 g versus 2315 ± 523 g; p < 0.001, 95% confidence interval 193 to 246 g). Perinatal mortality was also significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
1
2
1
Order By: Relevance
“…Prematurity and low birth weight are associated with a higher risk of perinatal death. 1,30 Gestational age at birth did not show any significant difference in the current analysis; however, twin pregnancy is known to be associated with higher rates of preterm birth before 34 weeks when compared to single pregnancies (42.3% and 36.7%, respectively). This is of utmost importance since early PTB is associated with higher rates of perinatal morbidity and death.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Prematurity and low birth weight are associated with a higher risk of perinatal death. 1,30 Gestational age at birth did not show any significant difference in the current analysis; however, twin pregnancy is known to be associated with higher rates of preterm birth before 34 weeks when compared to single pregnancies (42.3% and 36.7%, respectively). This is of utmost importance since early PTB is associated with higher rates of perinatal morbidity and death.…”
Section: Discussioncontrasting
confidence: 62%
“…However, in the present study only admission to the NICU was associated with twin PTB. 30,31 Some neonatal complications are directly related to prematurity, including feeding difficulties, infection, respiratory distress syndrome, jaundice, cerebral hemorrhage, necrotizing enterocolitis, retinopathy, and anemia. In the present study, cerebral hemorrhage and necrotizing enterocolitis were more common in twin pregnancies, with a 1.5-fold increased risk for cerebral hemorrhage and nearly twice the risk for necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that, at the same gestational age, the prognosis for twins is better than singletons, and the current study confirmed those results 22 . These results suggest that when preterm labor is suspected or diagnosed or when the time of preterm delivery must be determined for any reason in the mother or fetus in Korea, it is desirable for the best prognosis of the neonate to maintain pregnancy actively until 35 weeks’ gestation for singletons and 33 weeks’ gestation for twins.…”
Section: Discussionsupporting
confidence: 89%
“…Ericson et al [33] found similar results in Swedish infants from 1973 to 1988. More recently, Jacquemyn et al [34] compared morbidity and mortality in singletons and twins from Flanders from 1998 to 1999. Twins of 24 to 27 weeks' gestation had higher neonatal mortality rates than singletons.…”
Section: Comparisons Of Outcome After Adjustment For Gestational Agementioning
confidence: 99%